A model of atropine-resistant theta oscillations in rat hippocampal area CA1 - Gillies, M; Traub, R; Lebeau, F; Davies, C; Gloveli, T; Buhl, E; Whittington, M (Wiley, 2002)
Theta frequency oscillations are a predominant feature of rhythmic activity in the hippocampus. We demonstrate that hippocampal area CA1 generates atropine‐resistant theta population oscillations in response to metabotropic glutamate receptor activation under conditions of reduced AMPA receptor activation. This activity occurred in the absence of inputs from area CA3 and extra‐ammonic areas. Field theta oscillations were co‐expressed with pyramidal distal apical dendritic burst spiking and were temporally related to trains of IPSPs with slow kinetics. Pyramidal somatic responses showed theta oscillations consisted of compound inhibitory synaptic potentials with initial IPSPs with slow kinetics followed by trains of smaller, faster IPSPs. Pharmacological modulation of IPSPs altered the theta oscillation suggesting an inhibitory network origin. Somatic IPSPs, dendritic burst firing and stratum pyramidale interneuron activity were all temporally correlated with spiking in stratum oriens interneurons demonstrating intrinsic theta‐frequency oscillations. Disruption of spiking in these interneurons was accompanied by a loss of both field theta and theta frequency IPSP trains. We suggest that population theta oscillations can be generated as a consequence of intrinsic theta frequency spiking activity in a subset of stratum oriens interneurons controlling electrogenesis in pyramidal cell apical dendrites.